A force measuring microsystem based on electrothermal V-shaped actuator - Phuc, Pham Hong (Vietnam Journal of Mechanics, 2020)
This paper describes design and calculation of an electrothermal V-shaped actuator (EVA) and an amplification mechanism integrated into a force measuring microsystem (FMMS), aims to apply for characterization of a micro beam. Displacement and driving force are generated by thermal expansion of the V-shaped silicon beams while applying a voltage to the electrodes of the EVA. ANSYS simulation helps to find out the relations between thermal force and displacement corresponding to driving voltage and determine the temperature of V-shaped beam at various applying voltages. In our simulation, with applying voltage Um = 38 volt for six pairs of V-shaped beam, the maximal temperature of the beam reaches approximately to 1100°C and causes a melting phenomenon of the silicon beam. The additional amplification mechanism allows actuator’s displacement to be 6 times larger than before the improvement, thus the bending deformation of the micro beam can be seen perfectly, i.e. the force loading on the beam can be computed more exactly via a measured displacement of the beam tip. In addition, this FMMS has smaller size and supplies a larger beam’s deformation at the same voltage in comparison with previous design.